A Bayesian Approach to Andean Faunal Assemblages. Issue 2 (June 2019) - Osborn, Jo
Abstract : Faunal assemblages offer rich data for exploring domestication, subsistence, ritual practice, and political economy. Issues of equifinality, however, frequently complicate interpretations because different agents and processes may create similar archaeological signatures. Analysts are often forced to make interpretations based on qualitative observations, which can be difficult to justify or replicate. I present an alternative method for classifying Andean assemblages by using ethnographic, ethnohistoric, and archaeological data to construct a Bayesian network model. The model is assessed using specifically constructed test datasets and archaeological case studies. Bayesian models can lead to explicit and quantifiable probabilistic interpretations of faunal assemblages. Abstract : Los conjuntos óseos faunísticos constituyen una fuente importante de datos que permite explorar temas tan diversos como domesticación, subsistencia, prácticas rituales y economía política. Sin embargo, existen problemas de equifinalidad que pueden dificultar las interpretaciones de los conjuntos, ya que diferentes agentes y procesos pueden generar resultados arqueológicos similares. Los zooarqueólogos frecuentemente se ven obligados a hacer interpretaciones basadas en observaciones cualitativas, que pueden ser difíciles de justificar o reproducir. Este artículo presenta un método alternativo para clasificar los conjuntos faunísticos andinos mediante el uso de datos etnográficos, etnohistóricos y arqueológicos para construir un modelo bayesiano. El modelo se evalúa utilizando conjuntos de datos de prueba construidos específicamente y de estudios arqueológicos. El uso de modelos bayesianos puede llevar a interpretaciones probabilísticas explícitas y cuantificables sobre conjuntos zooarqueológicos.